READINESS OF NURSING STUDENTS IN ENTERING CLINICAL PRACTICE: A STUDY OF PHENOMENOLOGY - Hutapea, Adventina Delima; Damainov, Deony Aktivini; Quiensy, Divanca; Salakory, Gaat Gideon; Situmorang, Komilie (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The government's policy requires all parties to prepare for the New Normal stage, including the education sector. During the new normal era, online learning has shifted to limited face-to-face learning with the implementation of health protocols. Such a situation can affect student learning readiness which is adjusted to the conditions, legal basis, and the learning process in general. This study aimed to explore the experiences of nursing students' readiness to enter clinical practice. The research method used qualitative with a descriptive phenomenological study approach. The population was nursing students' batch 2020 at a West Indonesia Private University with a purposive sampling was 5 participants, data saturated. The research instrument used in-depth, semi-structured interviews conducted by the researcher. Five themes emerged namely increasing knowledge of nursing students in theory and practice, preparing physically to enter clinical practice, mental preparation to enter clinical practice, nursing students' perceptions of clinical practice, and motivation of nursing students to prepare for clinical practice. Nursing students prepare themselves physically, mentally, and emotionally and increase their knowledge to enter clinical practice to improve their skills and not cause errors, anxiety, and doubts. Further examination of the influencing factors of nursing students’ readiness to enter clinical practice is required.